The Effectiveness of a Football-Based Psychological Skills Training Program on Adolescents in the Indonesian–Malaysian Border Area: An Experimental Study in Entikong - Soemardiawan, Soemardiawan; Gustian, Uray (Indonesian Journal of Physical Education and Sport Science, 2026)
The Indonesia-Malaysia border region faces complex socio-economic challenges, including limited access to structured education and training. For this purpose, efforts to build psychological skills such as emotion regulation, stress management, and self-confidence are important to build resilience in the face of competitive and social pressures. This study aims evaluated the effectiveness of a football-based psychological skills training program for students in this area. Using an experimental design with control and experimental groups, 60 male students aged 15–16 participated in a 16-week program combining training sessions and football competitions. Psychological skills were measured with the Psychological Skills Inventory for Sports (PSIS-R5), and data were analyzed using One-way ANOVA. Results showed that the experimental group achieved significantly greater improvements in psychological skills than the control group (p < 0.000). Beyond enhancing mental readiness for competition, the program fostered social skills, team solidarity, and community engagement. These findings suggest that football-based psychological skills training can strengthen both individual resilience and social inclusion in border regions. Further research is recommended to assess the long-term effects and applicability of this approach to diverse populations.